UPAYA PENYELESAIAN PERMASALAHAN LINGKUNGAN HIDUP OLEH PEMERINTAH KABUPATEN SUKOHARJO: Resolving the Environmental Problems by Sukoharjo Regency Government - Nur Azizah Ayu Salsabilla; Yogo Pamungkas (Reformasi Hukum Trisakti, 2025)
Law Number 23 of 2014 grants Regional Governments the authority to protect, manage, and solve environmental issues within their jurisdiction. This research aims to identify the type of violation committed by PT RUM against the environment according to laws and regulations, as well as evaluate the effectiveness of the settlement between PT RUM and the community by the Sukoharjo Regency Government. The research follows a normative legal research approach, using secondary data as the primary source and interviews for supporting data. The research result and concludes that PT RUM has committed various violations, including improper pipe installation, failure to meet environmental quality standards, water and air pollution, and human rights violations. According to Appendix to Law Number 23 of 2014, the Sukoharjo Regency Government is responsible for supervising activities that require environmental permits and PPLH permits.